2021
DOI: 10.21775/cimb.041.001
|View full text |Cite
|
Sign up to set email alerts
|

Invasion of the Nervous System

Abstract: In vertebrates, the nervous system (NS) is composed of a peripheral collection of neurons (the peripheral nervous system, PNS), a central set found in the brain and spinal cord (the central nervous system, CNS). The NS is protected by rather complicated multi-layer barriers that allow access to nutrients and facilitate contact with the peripheral tissues, but block entry of pathogens and toxins. Virus infections usually begin in peripheral tissues and if these barriers are weakened, they can spread into the PN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 219 publications
1
6
0
Order By: Relevance
“…3). Inhibition of superinfection in vitro at a cellular level has been reported for many viral families (Beperet et al, 2014;Berngruber et al, 2010;Biryukov and Meyers, 2018;Webster et al, 2013), including members of the family Herpesviridae (Chase et al, 1990;Criddle et al, 2016;Koyuncu et al, 2021;Provost et al, 2017), and can occur as early as 2-6 h PI (Banfield et al, 2003;Meurens et al, 2004). To the best of our knowledge, such rapid and extreme inhibition of superinfection that we observed with CyHV-3 has not been described for other viruses, and thus opens up multiple avenues for further investigation into the underlying mechanisms.…”
Section: Discussionsupporting
confidence: 48%
“…3). Inhibition of superinfection in vitro at a cellular level has been reported for many viral families (Beperet et al, 2014;Berngruber et al, 2010;Biryukov and Meyers, 2018;Webster et al, 2013), including members of the family Herpesviridae (Chase et al, 1990;Criddle et al, 2016;Koyuncu et al, 2021;Provost et al, 2017), and can occur as early as 2-6 h PI (Banfield et al, 2003;Meurens et al, 2004). To the best of our knowledge, such rapid and extreme inhibition of superinfection that we observed with CyHV-3 has not been described for other viruses, and thus opens up multiple avenues for further investigation into the underlying mechanisms.…”
Section: Discussionsupporting
confidence: 48%
“…The use of PRV for viral tracing has benefited from mechanistic studies that have defined the role of virally encoded proteins in invasiveness, transsynaptic passage, and virulence (Mettenleiter, 2000; Pomeranz et al., 2005; Mettenleiter et al., 2008; Koyuncu et al., 2021; Engel et al., 2015). These studies have identified attenuated strains useful for transneuronal analysis, and defined model systems that have proven to be of great value in defining the viral life cycle.…”
Section: Introductionmentioning
confidence: 99%
“…These concerns were addressed in a number of laboratories through detailed studies of the viral life cycle and the function of gene products in the viral genome. The latter proved to be particularly important in the engineering of strains of virus that were reduced in virulence, were transported selectively in the retrograde direction through neural circuitry, and expressed unique reporters of infection (Koyuncu et al., 2021; Pomeranz et al., 2005). Evidence regarding the specificity of viral transport through neural circuits has continued to accumulate as application of the method has become a staple of circuit studies and the tools available have become increasingly powerful.…”
Section: Introductionmentioning
confidence: 99%
“…Neuroinvasive viruses are capable of infecting both the peripheral and central nervous systems. Natural or nosocomial neuroinvasive virus infections are often acutely severe, causing a variety of neuropathies, demyelinating disease, meningitis, and encephalitis [1,2]. It is also clear that some viruses, like the alpha herpesviruses (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…herpes simplex viruses, and varicella-zoster virus) can also spread to the central nervous system asymptomatically or sub-clinically, where they may cause chronic or recurrent neuroinflammation and trigger the development of neurodegenerative diseases like Alzheimer's [3]. While the spread of these viruses within the nervous system is not entirely understood, researchers have taken advantage of their neuroinvasive properties as neuroanatomical circuit tracing tools [2,4,5].…”
Section: Introductionmentioning
confidence: 99%